Platinum accumulation in chemotherapy: toxicity mechanisms, challenges, and mitigation strategies - Yier Lai; Guodong Qiu; Zhiwei Zheng; Xiaoting Huang; Pi Guo; Yuling Zhang; Ling Fang (BioMetals, 2026)
Platinum-based chemotherapeutic agents constitute the cornerstone of treatment for a wide range of solid tumors. However, residual platinum can persist in the body long after treatment cessation, leading to progressive accumulation, chronic multi-system toxicity, and significant impairment of patients' quality of life. The insidious onset and lack of specific monitoring methods often lead to the oversight of this treatment-related metal accumulation toxicity. This article reviews the environmental and occupational exposure risks of platinum, its unique pharmacokinetic properties, and elucidates how its irreversible binding to proteins and accumulation within mitochondria form the chemical basis for its long-term toxicity. It further elaborates on the core mechanisms underlying platinum accumulation-mediated multi-organ toxicity, including nephrotoxicity, neurotoxicity, and ototoxicity. The aim is to provide insights and directions for improving the long-term prognosis of cancer survivors by clarifying the toxicological mechanisms, clinical impacts, and future strategies for mitigating platinum-induced metal accumulation.

Unveiling forest vertical structure across China through stratified effective plant area index using extensive UAV LiDAR and multi-source remote sensing data - Zhiyong Qi; Zitong Bai; Haitao Yang; Yao Wang; Kai Cheng; Zekun Yang; Ang Chen; Tianyu Xiang; Yu Ren; Yixuan Zhang; Yuling Chen; Qingpeng Wang; et al. (Remote Sensing of Environment, 2026)

Effects of squat load and velocity on neuromuscular control strategies - Xingchen Zhang; Yao Li; Yuling Fang; Danyang Kou; Hanbing Wu; Yuan Gao; Lian Duan (European Journal of Applied Physiology, 2026)

Prepare the umbrella before it rains: Transmission and rescue strategy of extreme climate shocks via susceptible-infectious-recovered-susceptible model - Qian Wang; Fang Nan; Yuling Luo (Ecological Economics, 2026)

Characteristics and source apportionment of atmospheric fine particulate-bound mercury (PBM2.5) in abandoned mercury mining areas in southwestern China - Yuling Kuang; Longchao Liang; Shasha Liu; Xian Dong; Fang Zhu; Xiaohang Xu; Zhuo Chen; Yayun Li; Yaji Li; Guangle Qiu (Acta Geochimica, 2026)

Cellulose-based ultralight foam with dual-scale porosity from hybrid fibers for sustainable oil-water separation - Weiqiang Li; Jingge Liu; Meiying Li; Haitao Lin; Jian Fang; Xiaoqiao Wang; Jianchu Xu; Yuling Li; Junze Zhang; Xinheng Li; Gang Li (Carbohydrate Polymers, 2026)

The plant ontology of cell types - Hongyu Chen; Pu Liang; Xiaolin Lu; Shuai Jiang; Jingjing Jin; Jiaqi Cai; Yaqian Lu; Dihuai Zheng; Jie Yao; Qinjie Chu; Huixia Shou; Chengxin Fu; et al. (Molecular Plant, 2026)

Effect of Limosilactobacillus fermentum NCU001464 fermentation on physicochemical properties, xanthine oxidase inhibitory activity and flavor profile of Pueraria Lobata - Siyun Huang; Xin Yin; Yuling Fang; Tao Xiong; Fei Peng (Food Chemistry, 2025)

Influences of natural organic acids on the degradation of atrazine in water by pyrite-mediated Fenton oxidation - Yuling Zheng; Fang Li; Chen Yan; Wei Yang; Jia Wen; Biao Song (Journal of Water Process Engineering, 2025)

Fabrication and characterization of lysozyme fibrils/Zein complexes for resveratrol encapsulation: Improving stability, antioxidant and antibacterial activities - Min Huang; Yuling Song; Han Wang; Hao Li; Rongmi Zhou; Qing Cao; Lijuan Dong; Gerui Ren; Di Wu; Qunfang Lei; Wenjun Fang; Dan Deng; et al. (Food Chemistry, 2025)

Effects of OSA-starch-fatty acid interactions on the structural, digestibility and release characteristics of high amylose corn starch - Mingyue Liu; Xiaoyan Wang; Yihui Li; Danni Jin; Yuling Jiang; Yong Fang; Qinlu Lin; Yongbo Ding (Food Chemistry, 2024)

Expert Consensus on Big Data Collection of Skin and Appendage Disease Phenotypes in Chinese - Shuang Zhao; Zhongling Luo; Ying Wang; Xinghua Gao; Juan Tao; Yong Cui; Aijun Chen; Daxing Cai; Yan Ding; Heng Gu; Jianying Gu; Chao Ji; et al. (Phenomics, 2024)

Site-directed immobilization of enzymes on nanoparticles using self-assembly systems - Haili Zhou; Yuling Fang; Jing Zhang; Tao Xiong; Fei Peng (Bioresource Technology, 2024)

Characterization, in vitro digestibility and release properties of starch-linoleic acid-sodium alginate composite film - Huirong Chen; Xiaoyan Wang; Danni Jin; Mingyue Liu; Xiaonian Wu; Yuling Jiang; Yong Fang; Qinlu Lin; Yongbo Ding (Food Research International, 2023)

A chronostratigraphic and biostratigraphic framework for the Yanliao Biota of northeastern China: Implications for Jurassic terrestrial ecosystems and evolution - Yuling Li; Su-Chin Chang; Haichun Zhang; Jun Wang; Rui Pei; Daran Zheng; Yan Fang; Sidney R. Hemming (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Comparative Analysis of the Therapeutic Effects of Fresh and Cryopreserved Human Umbilical Cord Derived Mesenchymal Stem Cells in the Treatment of Psoriasis - Zhifeng Wang; Yifan Hu; Xiaoyu Wang; Youdong Chen; Danfeng Wu; Houli Ji; Cuicui Yu; Jingmeng Fang; Chunrong Pan; Lianjian Wang; Shouxin Wang; Yinhong Guo; et al. (Stem Cell Reviews and Reports, 2023)

Effect of amylose content and crystal type on the structure and digestibility of starch-fatty acid complex nanoparticle - Mingyue Liu; Xiaonian Wu; Xiaoyan Wang; Yuling Jiang; Zhengyu Huang; Yong Fang; Qinlu Lin; Yongbo Ding (Food Structure, 2023)

Fungicide exposure accelerated horizontal transfer of antibiotic resistance genes via plasmid-mediated conjugation - Houpu Zhang; Jiajin Song; Zhiruo Zheng; Tongxin Li; Nan Shi; Yuling Han; Luqing Zhang; Yunlong Yu; Hua Fang (Water Research, 2023)

Estimating the prevalence of hypertension in 164 cities in China by wastewater-based epidemiology - Chenzhi Hou; Yuling Zhong; Lan Zhang; Muyuan Liu; Fang Yan; Mengyi Chen; Youmei Wang; Peng Xu; Mengxiang Su; Chi Hu; Bin Di (Journal of Hazardous Materials, 2023)

PiRNA pathway in the cardiovascular system: a novel regulator of cardiac differentiation, repair and regeneration - Yuling Zhou; Ya Fang; Cuilian Dai; Yan Wang (Journal of Molecular Medicine, 2021)

Analysis of allelic variants of RhMLO genes in rose and functional studies on susceptibility to powdery mildew related to clade V homologs - Peihong Fang; Paul Arens; Xintong Liu; Xin Zhang; Deepika Lakwani; Fabrice Foucher; Jérémy Clotault; Juliane Geike; Helgard Kaufmann; Thomas Debener; Yuling Bai; Zhao Zhang; et al. (Theoretical and Applied Genetics, 2021)
Key message Rose has 19 MLO genes. Of these, RhMLO1 and RhMLO2 were shown to be required for powdery mildew infection, which suggests their potential as susceptibility targets towards disease resistance. Abstract Powdery mildew, caused by Podosphaera pannosa , is one of the most serious and widespread fungal diseases for roses, especially in greenhouse-grown cut roses. It has been shown that certain MLO genes are involved in powdery mildew susceptibility and that loss of function in these genes in various crops leads to broad-spectrum, long-lasting resistance against this fungal disease. For this reason, these MLO genes are called susceptibility genes. We carried out a genome-wide identification of the MLO gene family in the Rosa chinensis genome, and screened for allelic variants among 22 accessions from seven different Rosa species using re-sequencing and transcriptome data. We identified 19 MLO genes in rose, of which four are candidate genes for functional homologs in clade V, which is the clade containing all dicot MLO susceptibility genes. We detected a total of 198 different allelic variants in the set of Rosa species and accessions, corresponding to 5–15 different alleles for each of the genes. Some diploid Rosa species shared alleles with tetraploid rose cultivars, consistent with the notion that diploid species have contributed to the formation of tetraploid roses. Among the four RhMLO genes in clade V, we demonstrated using expression study, virus-induced gene silencing as well as transient RNAi silencing that two of them, RhMLO1 and RhMLO2 , are required for infection by P. pannosa and suggest their potential as susceptibility targets for powdery mildew resistance breeding in rose.

Genetic Architecture of Childhood Kidney and Urological Diseases in China - Ye Fang; Hua Shi; Tianchao Xiang; Jiaojiao Liu; Jialu Liu; Xiaoshan Tang; Xiaoyan Fang; Jing Chen; Yihui Zhai; Qian Shen; Guomin Li; Li Sun; et al. (Phenomics, 2021)
Kidney disease is manifested in a wide variety of phenotypes, many of which have an important hereditary component. To delineate the genotypic and phenotypic spectrum of pediatric nephropathy, a multicenter registration system is being implemented based on the Chinese Children Genetic Kidney Disease Database (CCGKDD). In this study, all the patients with kidney and urological diseases were recruited from 2014 to 2020. Genetic analysis was conducted using exome sequencing for families with multiple affected individuals with nephropathy or clinical suspicion of a genetic kidney disease owing to early-onset or extrarenal features. The genetic diagnosis was confirmed in 883 of 2256 (39.1%) patients from 23 provinces in China. Phenotypic profiles showed that the primary diagnosis included steroid-resistant nephrotic syndrome (SRNS, 23.5%), glomerulonephritis (GN, 32.2%), congenital anomalies of the kidney and urinary tract (CAKUT, 21.2%), cystic renal disease (3.9%), renal calcinosis/stone (3.6%), tubulopathy (9.7%), and chronic kidney disease of unknown etiology (CKDu, 5.8%). The pathogenic variants of 105 monogenetic disorders were identified. Ten distinct genomic disorders were identified as pathogenic copy number variants (CNVs) in 11 patients. The diagnostic yield differed by subgroups, and was highest in those with cystic renal disease (66.3%), followed by tubulopathy (58.4%), GN (57.7%), CKDu (43.5%), SRNS (29.2%), renal calcinosis /stone (29.3%) and CAKUT (8.6%). Reverse phenotyping permitted correct identification in 40 cases with clinical reassessment and unexpected genetic conditions. We present the results of the largest cohort of children with kidney disease in China where diagnostic exome sequencing was performed. Our data demonstrate the utility of family-based exome sequencing, and indicate that the combined analysis of genotype and phenotype based on the national patient registry is pivotal to the genetic diagnosis of kidney disease.

Nanoscale zerovalent iron-mediated degradation of DDT in soil - Yuling Han; Nan Shi; Huifang Wang; Xiong Pan; Hua Fang; Yunlong Yu (Environmental Science and Pollution Research, 2016)

Expression, purification and characterization of pectate lyase A from Aspergillus nidulans in Escherichia coli - Qingxin Zhao; Sheng Yuan; Yuling Zhang; Hong Zhu; Chuanchao Dai; Fang Yang; Fengmin Han (World Journal of Microbiology and Biotechnology, 2007)

The changing regional distribution of grain production in China in the 21st century - Peihong Yin; Xiuqi Fang; Qing Tian; Yuling Ma (Journal of Geographical Sciences, 2006)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)